Scaling up evidence-based digital early life nutrition interventions in a county setting: an implementation trial – protocol for Phase 2 of the Nutrition Now project - Medin, Anine Christine; Vik, Frøydis Nordgård; Helle, Christine; Helland, Sissel Heidi; Wills, Andrew Keith; Osorio, Natalie Garzon; Lian, Henrik; Ersfjord, Torunn Iveland; Van Daele, Wim; Bjørkkjær, Tormod; Valen, Erlend Nuland; Gebremariam, Mekdes Kebede; et al. (Frontiers in Public Health, 2024)
Background: Few effective health interventions transition from smaller efficacy or effectiveness studies to real-world implementation at scale, representing a gap between evidence and practice. Recognising this, we have developed Nutrition Now – a tailored digital resource building on four efficacious dietary interventions, aiming to improve nutrition in the important first 1000 days of life. Nutrition Now targets and guides expectant parents and parents of 0–2-year-olds, serves as a reliable source of evidence-based information for midwives and public health nurses at maternal and child healthcare (MCH) centres, and offers pedagogical tools for early childhood education and care (ECEC) staff. The aim of this study is to implement Nutrition Now at scale and evaluate the impact of different sets of multifaceted implementation strategies on implementation outcomes. Methods: A quasi-experimental design with three study arms will be used, providing either low, medium or high implementation support, when rolled out in 50 municipalities in 2 counties in Norway. Nutrition Now will be implemented in MCH and ECEC settings and made available to expectant parents and parents of 0–2-year-olds through social media and MCH. The implementation support builds on strategies described in the Expert Recommendations for Implementing Change (ERIC) implementation framework and is informed by dialogues with stakeholders. Impact of the different degree of implementation support will be assessed by examining total use, reach, adoption, fidelity, and sustainability using usage data generated as part of the Nutrition Now resource, publicly available municipal data and qualitative interviews with MCH and ECEC staff. Discussion: Nutrition Now Phase 2 will break new ground by scaling up successively delivered and complementary dietary interventions in the first 1000 days of life in a real-life context. The project also seeks to identify what level of implementation support is most effective when implementing digital, scalable, evidence-based early-life nutrition interventions in community settings. The project will inform implementation research and provide knowledge about effective implementation strategies to be used in a national scale-up of Nutrition Now.